Resistance sources to root-knot nematode Meloidogyne enterolobii in Solanum species - Pinheiro, Jadir Borges; Silva, Giovani Olegario da; Jesus, Jhenef Gomes de; Biscaia, Danielle; Melo, Raphael Augusto de Castro e (Emirates Journal of Food and Agriculture, 2020)
The objective of this work was to prospect sources of resistance to root-knot nematode Meloidogyne enterolobii in Solanum species with potential to be used as rootstocks for cultivated Solanaceae. Nine accessions of Solanum sessiliflorum, 27 accessions of S. lycocarpum, 21 accessions of S. acanthodes, 22 accessions of S. scinericum and 26 accessions of S. scuticum for resistance to M. enterolobii. Rutgers and Nemadoro tomatoes were used as susceptible and resistant controls, respectively. The experiment was conducted in a greenhouse at Embrapa Vegetables, Brasília-DF, Brazil, in a completely randomized design with six replications. The experimental unit was a represented by a single plant grown in a plastic pot containing 3 L of substrate. 4000 eggs and eventual juveniles of second stage M. enterolobii were inoculated per pot. At 119 days after inoculation, gall index (Gi), egg mass index (EMI), number of eggs per root gram (NE) and reproduction factor (Fr) were evaluated. Data were subjected to analysis of variance and grouping of treatments by Scott-Knott. It was verified that S. acanthodes and S. Lycocarpum are species with high resistance to M. enterolobii, with accessions being classified identified as immune. S. scuticum also has great potential, as several resistant accessions were identified, although some accessions were quite susceptible; whereas for S. subinerme only 4 resistant accessions were identified, although all others presented a reproduction factor much lower than tomato cv. Nemadoro as control; and all evaluated S. sessiliflorum accessions were susceptible.